CTNI-07. LOMUSTINE/TEMOZOLOMIDE CHEMOTHERAPY FOR NEWLY DIAGNOSED MGMT-METHYLATED IDHWT GLIOBLASTOMA ACCORDING TO CETEG/NOA-09: REAL-WORLD EXPERIENCE IN A MULTICENTER COHORT. (14th November 2022) - Weller, Johannes; Zeyen, Thomas; Schlegel, Uwe; Lazaridis, Lazaros; Werner, Jan-Michael; Onken, Julia; Zeiner, Pia; Drexler, Richard; Hau, Peter; Seidel, Clemens; Grosse, Lucia; Clusmann, Hans; et al.
Abstract: INTRODUCTION: The CeTeG/NOA-09 trial demonstrated superior median overall survival (mOS, 48.1 months) in MGMT-methylated glioblastoma treated with lomustine/temozolomide compared to temozolomide. We retrospectively analyzed an off-study cohort of patients treated with lomustine/temozolomide to gather real-world data on this new regimen. METHODS: Adult patients from 20 centers in Germany, Austria and Switzerland were included. Inclusion criteria were MGMT-methylated IDHwt glioblastoma newly diagnosed prior to end of 2020, and lomustine/temozolomide treatment as part of first-line therapy. RESULTS: 321 patients with a median age of 57 years (range, 21-78) and a median follow-up of 19.9 months were included. In the whole cohort, mOS was 41.0 months (95%CI, 33.0 – not reached). In patients starting lomustine/temozolomide immediately upon initiation of radiotherapy strictly following the CeTeG protocol (88%), mOS was 52.8 months (35.8 – not reached) as compared to 24.6 months (17.6 – not reached) in patients starting lomustine/temozolomide after completion of radiotherapy/concomitant temozolomide (12%, logrank test: p = 0.06). Patients with a KPS < 80 had a shorter mOS of 19.7 months (95%CI, 16.6 – not reached) compared to 41.0 months (33.0 – not reached, p = 0.009) in KPS 80-100. Gross total resection (GTR, 53.9%) was associated with longer mOS (52.8 months, 95%CI 24.1 – not reached) compared to partial resection/biopsy (30.5 months, 95%CI 36.8 – not reached, p=0.004). Multivariable Cox regression analysis confirmed GTR (HR 0.66, p = 0.033) and younger age ( ≤ 50 years: HR 0.42, p = 0.001), but not KPS (80-100 vs. lower: HR 0.66, p = 0.12) as independent prognostic factors. DISCUSSION: In this real-world multicenter cohort, survival was similar to the promising results of CeTeG/NOA-09. Further analyses should investigate a potentially reduced benefit from lomustine/temozolomide in patients with low KPS/no GTR and a possible detrimental effect from deferred lomustine/temozolomide initiation. The median follow-up is admittedly short, updated data will be presented.